(untitled) (Adhyayan Journal, 2026)
The primary focus of this study is to analyze the application of structuralism in the interpretation of Lokayat (folk narrative). The primary objective of this research is to ascertain the relevance of structuralist principles in the analysis of folk narratives as delineated in this text. The study has been conducted using a structuralist analytical framework, explicitly focusing on mythological structuralism, and by examining the mythic form of the chosen narrative. To enhance the studys theoretical framework, concepts from subsequent structuralist theorists, including Bronislaw Malinowski and the religious existentialist Mircea Eliade, have been incorporated as supplementary theoretical perspectives. Utilizing qualitative research methodology, this study analyzes 36 folk narratives within the text, organizing them into thematic categories and examining their mythic structures through the lens of underlying binary oppositions. In this process, the folk narrative has been established both as a description of historical facts (diachronic, temporal) and as a mythic formula that provides moral and ethical justification to political power and authority (synchronic, timeless). The study employs qualitative research methods to delineate binary oppositions, including order/ chaos, nature/ culture, human/ divine, heroism/ compassion, war/ peace, present/ past, and happiness/ sorrow, within the chosen narratives, and investigates the logical resolution of these oppositions. The internal structure of the narrative is elucidated as a cultural mechanism that converts social and political chaos into a stable governance system via the heros sacrificial offering. The study concludes that the folk narrative transcends a mere linear recounting of 36 episodes; it persists as a complex cultural framework that symbolically reconciles profound conflicts inherent in human consciousness.